Cultural reification in Circassian diaspora: Stereotypes, prejudices and ethnic relations - Kaya, Ayhan (Routledge Journals, Taylor & Francis Ltd, 2005)
Contemporary diaspora identities differ to a certain extent from conventional forms of diasporic formations in the sense that the former are no longer characterised by the overwhelming wish to return. Contemporary diasporas are built upon two principal pillars: modern communicative circuitry, and acts of exclusion by receiving societies. Deported by the Russians from their homeland in the last quarter of the nineteenth century, Circassian tribes were welcomed by the Ottoman Empire for practical reasons. Since then they have been subject to several acts of both inclusion and exclusion by the Turkish Republic. They were also treated differently by their local neighbour groups. This paper claims that Circassian groups in diaspora have generated distinct ethnic and cultural identities depending on how they were recognised, or unrecognised, both by their neighbours and by the Turkish state. Cultural reification, or essentialisation, becomes common practice among diaspora groups, providing them with a safe haven against misrepresentation, prejudice, exclusion and discrimination. Cultural reification not only adds to the construction of a sense of communality, but also serves as a way of doing politics for the Circassians in diaspora. Culture, then, not only remains a heritage, but also becomes a political strategy.
Keywords: Circassians; Diaspora; İdentity; Cultural Reification; Turkey; Stereotypes; Identity